The sustainability of the Pegat Lake as the centre for the orientation of the Giri kingdom, socio-cultural studies. Issue 1 (1st March 2022) - Koderi, M; Soemardiono, B; Faqih, M
Abstract: The synergy between environmental sustainability and technological progress is the key to sustainable development. The dependence of the people of the Giri Kingdom on the Pegat Lake as a source of clean water as well as the orientation centre of the Giri Kingdom's downtown area, has shifted due to the development of the city and advances in clean water technology. The potential for socio-cultural sustainability which is based on the existence of Pegat Lake is the strength of the meaning of local wisdom which is a process of harmonious relationship between nature, humans and architecture is starting to be forgotten. This paper explores the role of Pegat Lake from time to time based on artefacts, data and history as well as notes on the results of previous research. The important finding of interdependence between the Pegat Lake area, the Giri Palace area and the Tomb and Ainul Yaqin Mosque area is a strength of sustainability to continue to be developed according to the socio-cultural demands of the community as well as the development of religious and historical-based ecotourism as an answer to sustainable regional development.